The complete mitochondrial genomes of five important medicinal Ganoderma species: Features, evolution, and phylogeny - Li, Qiang; Xiang, Dabing; Wan, Yan; Wu, Qi; Wu, Xiaoyong; Ma, Chengrui; Song, Yue; Zhao, Gang; Huang, Wenli (International journal of biological macromolecules, 2019)
In order to assess variation and conservation among Ganoderma species and reconstruct the phylogeny of the Ganoderma lucidum complex, complete mitogenomes of five Ganoderma species were sequenced and successfully assembled. The five Ganoderma mitogenomes were all composed of circular DNA molecules, with lengths ranging from 57,232 bp to 124,588 bp. Mitogenomic synteny analysis revealed several gene rearrangements among Ganoderma mitogenomes. Across the 14 core protein-coding genes (PCGs) tested, atp8 and atp9 had the least genetic distance among the Ganoderma species we investigated, indicating that the two genes were highly conserved. In addition, the Ka/Ks values for all 14 core PCGs were <1, suggesting that these genes were subject to purifying selection. Comparative mitogenomic analysis indicated that the increase in intron number contributed to expansion of the mitogenome in Polyporales. Phylogenetic analyses based on two combined mitochondrial gene datasets yielded an identical and well-supported (BPP ≥ 0.95) topology that divided the nine Ganoderma species into three groups. This study is the first to reveal large-scale gene rearrangements in Ganoderma mitogenomes. The results presented herein will further promote investigations of the genetics, evolution and phylogeny of the Ganoderma lucidum complex.